A Comparative Assessment to Evaluate Enhanced External Counter Pulsation Effect on Physical Profile and Quality of Life in Diabetic and Nondiabetic Coronary Heart Disease Patients - Vikram Singh & , Girija Kumari & , Bimal Chhajer, Ashok Kumar Jhingan, Saurabh Dahiya (Journal of Applied Pharmaceutical Science, 2018)
This study was conducted to assess the effect of Enhanced External Counter Pulsation (EECP) on physical profile and Health-Related Quality of Life (HRQoL) in diabetic and nondiabetic Coronary Heart Disease (CHD) patients. This pretest-posttest designed prospective study was conducted among 163 diabetic and nondiabetic coronary heart disease patients in the SAAOL Heart Center, New Delhi. The physical profile of study subjects was assessed through Cooper’s 12 minutes’ walk test, Canadian Cardiovascular Society (CCS) angina scale and Medical Research Council (MRC) dyspnea scale. The HRQoL of subjects was assessed using SF-36 (short form) and Seattle Angina Questionnaire (SAQ) scale. A significant improvement was observed in blood pressure, heart rate, SpO2, VO2 max, CCS angina and MRC score in both the groups from baseline to 12 months. Significant improvement was also observed in both the scales of HRQoL after EECP treatment at 12 months follow up in all the health domains of SF-36 & SAQ scale with special reference to angina severity and angina stability improvement. In conclusion, EECP is an effective non-invasive therapy to treat diabetic and nondiabetic CHD patients. This non-invasive procedure may improve the physical functional capacity, angina, dyspnea and overall HRQoL of diabetic and nondiabetic CHD patients.
Keywords: Coronary Heart Disease, Diabetes Mellitus, Angina Pectoris, Health-Related Quality of Life, Enhanced External Counter Pulsation.